Effect of Health Education on Adolescent Knowledge and Attitudes Regarding Early Marriage - Paikah Ulandari; Apriani Susmita Sari (Omni Nursing Journal, 2024)
Background: Early marriage remains a critical public health issue that exposes adolescents to increased risks of infection, pregnancy complications, miscarriage, and even mortality. These risks are often exacerbated by limited access to health education among adolescents, especially in rural areas. Health education plays a vital role in promoting physical, psychological, social, and economic well-being. Objective: This study aimed to determine the effect of health education on adolescent knowledge and attitudes regarding early marriage. Methods: This research utilized a pre-experimental approach with a one group pretest-posttest. The sampling technique was Stratified random sampling. The respondents in this study were 48 respondents. The questionnaire used in this study was a questionnaire on knowledge about early marriage and attitudes towards early marriage. Analysis of test used was the Wilcoxon test. Results: There was an effect of health education on adolescent knowledge about early marriage with a significant value of 0.000 (p<0.05). There was an effect of health education on adolescent attitudes about early marriage with a significant value of 0.001 (p <0.05). Conclusion: Health education about early marriage affects the knowledge and attitudes of adolescents with the hope that adolescents will be able to have a positive attitude if there is a desire to marry at an early age to prevent various impacts that may occur.